2013
DOI: 10.4103/2277-9175.115799
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the responses of succinate dehydrogenase, isocitrate dehydrogenase, malate dehydrogenase and glucose-6-phosphate dehydrogenase to acid shock generated acid tolerance in Escherichia coli

Abstract: Background:Escherichia coli have an optimum pH range of 6-7 for growth and survival that's why, called neutrophiles. The ΔpH across the cytoplasmic membrane is linked to cellular bioenergetics and metabolism of the body which is the major supplier of the proton motive force, so homeostasis of cellular pH is essential. When challenged by low pH, protons enter the cytoplasm; as a result, mechanisms are required to alleviate the effects of lowered cytoplasmic pH.Materials and Methods:The activities of Succinate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Bioinformatics analysis found that the ORF in pSL-2–41 encodes two domains (the malic and Malic_M domains) that form the N-terminal region of the malate dehydrogenase protein, but the acid-resistance assay indicated that this fragment is sufficient to allow E. coli to survive in this hostile environment. Jain’s group [32] confirmed that the hosts E. coli DH5α and E. coli W3110 can tolerate acidic pH with the help of malate dehydrogenase, which mainly functions to pump out protons and restore the cytoplasmic pH back to neutral. Here, the additional heterologous copy of the malate dehydrogenase from H. haemolyticus ( E. coli DH10B/pSL-2–41) can assist the host strain in tolerating the more hostile environment (pH 1.9) compared to the negative control ( E. coli DH10B/pSL), which indicated that exogenous insert may enhance the acid resistance of host bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis found that the ORF in pSL-2–41 encodes two domains (the malic and Malic_M domains) that form the N-terminal region of the malate dehydrogenase protein, but the acid-resistance assay indicated that this fragment is sufficient to allow E. coli to survive in this hostile environment. Jain’s group [32] confirmed that the hosts E. coli DH5α and E. coli W3110 can tolerate acidic pH with the help of malate dehydrogenase, which mainly functions to pump out protons and restore the cytoplasmic pH back to neutral. Here, the additional heterologous copy of the malate dehydrogenase from H. haemolyticus ( E. coli DH10B/pSL-2–41) can assist the host strain in tolerating the more hostile environment (pH 1.9) compared to the negative control ( E. coli DH10B/pSL), which indicated that exogenous insert may enhance the acid resistance of host bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies to withstand acid stress by sustained pH homeostasis have evolved in microbes (He et al 2017;Jain et al 2013;Liu et al 2016b;Lu et al 2013;Miller and Maier 2014;Sohlenkamp 2017). Some yeast and bacteria maintain a relatively stable and neutral intracellular pH (pH i ) in the presence of constantly changing extracellular pH (pH ex ) and generate unfixed proton gradients (Siegumfeldt et al 2000).…”
Section: Resistance Mechanisms Ph Homeostasismentioning
confidence: 99%
“…The PMF-dependent proton pump is one of the most important acid tolerance systems in bacteria in the maintenance of pH homeostasis, through which excess protons are pumped out from the cytoplasm (Jain et al 2013). Several proton pumps have been shown to promote proton efflux, such as the H + -ATPase, symporter, antiporter, and secondary transporter (Sun 2016).…”
Section: Enhancement Of Proton Pumpsmentioning
confidence: 99%
“…In E. coli, the expression is down-regulated by the aerobic respiration control protein (ArcA), particularly under anaerobic conditions (Park et al, 1995). When E. coli was grown on acid media, it raised not only the MDH activity but also the isocitrate dehydrogenase and succinate dehydrogenase activities (Jain et al, 2013).…”
Section: Transcriptional Regulation Of Mdh Genementioning
confidence: 99%